Comparative study of flexibility enhancement technologies for the coal-fired combined heat and power plant. (15th March 2019) - Zhao, Shifei; Ge, Zhihua; Sun, Jian; Ding, Yulong; Yang, Yongping
Highlights: The flexibility can be improved by the P2H mode and AHS mode. The operational strategies of both modes are presented and compared. Thermodynamic and techno-economic performances are investigated. The CHP plant consumes 3.34% less coal with the waste heat recovery. The net annual revenue of the TES system is 2.14 M$ higher. Abstract: The flexibility enhancement of the coal-fired combined heat and power (CHP) plant can contribute to both renewable energy integration and decarbonization. In this research, we classify the flexibility enhancement technologies into the "power to heat (P2H)" mode and "auxiliary heat source (AHS)" mode based on their principles and operational strategies. Then thermodynamic performances of both modes are compared with the designed heat load and one-day loads. After that, the techno-economic analysis is also conducted. Results show that with the designed heat load, the power load factor range of the CHP plant is extended from 54.87%–78.72% to 25.20%–100% with the AHS mode, and to 0–78.72% with the electric boiler. And compared to integration with the heat-only boiler, the coal consumption of CHP plant can be increased by 2.27% with the thermal energy storage (TES) system (Electric boiler), and reduced by 0.78%, 1.85%, 2.33%, 3.34% with the electric boiler, electric heat pump, TES system (Extraction steam) and waste heat recovery, respectively. The techno-economic analysis indicates that during the heating period, the net annual revenues of the TES system and electric boiler are 2.14 M$ and 1.71 M$ higher than that of the heat-only boiler. This study gives a methodology on choosing the technology to enhance the flexibility for the coal-fired CHP plant.